Increasing energy efficiency of hydrogen refueling stations via optimal thermodynamic paths (2024)
ABSTRACT: This work addresses the energy efficiency of hydrogen refueling stations (HRS) using a first- principles model and optimal control methods to find minimal entropy production operating paths. The HRS model shows good agreement with experimental data, achieving maximum state of charge and temperature discrepancies of 1 and 7%, respectively. Model solution and optimization is achieved at a relatively low computational time (40 s) when compared to models of the same degree of accuracy. The entropy production mapping indicates the flow control valve as the main source of irreversibility, accounting for 85% of the total entropy production in the process. The minimal entropy production refueling path achieves energy savings from 20 to 27% with respect to the SAE J2601 protocol, depending on the ambient temperature. Finally, the proposed method under near reversible refueling conditions shows a theoretical reduction of 43% in the energy demand with respect to the SAE J2601 protocol.